Enhanced photoinactivation of Staphylococcus aureus with nanocomposites containing plasmonic particles and hematoporphyrin. Issue 4 (27th June 2012) - Khlebtsov, Boris N.; Tuchina, Elena S.; Khanadeev, Vitaly A.; Panfilova, Elizaveta V.; Petrov, Pavel O.; Tuchin, Valery V.; Khlebtsov, Nikolai G.
Abstract We fabricated composite nanoparticles consisting of a plasmonic core (gold nanorods or gold–silver nanocages) and a hematoporphyrin‐doped silica shell. The dual photodynamic and photothermal activities of such nanoparticles against Staphylococcus aureus 209 P were studied and compared with the activities of reference solutions (hematoporphyrin or silica‐coated plasmonic nanoparticles). Bacteria were incubated with nanocomposites or with the reference solutions for 15 min, which was followed by CW light irradiation with a few exposures of 5 to 30 min. To stimulate the photodynamic and photothermal activities of the nanocomposites, we used LEDs (405 and 625 nm) and a NIR laser (808 nm), respectively. We observed enhanced inactivation of S. aureus 209 P by nanocomposites in comparison with the reference solutions. By using fluorescence microscopy and spectroscopy, we explain the enhanced antimicrobial effect of hematoporphyrin‐doped nanocomposites by their selective accumulation in the vicinity of the bacteria. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)